Pengembangan Kemampuan Mengajar Tutor dengan Metode Student Centered Learning Pada PKBM Bumi Literasi - Soraya Grabiella Dinamika; Dewi Shinta Wulandari Lubis (Forum Kerjasama Pendidikan Tinggi, 2021)
The government through the Ministry of Education and Culture has facilitated the community to be able to improve education and living standards through non-formal education (PNF), one of which is called the Community Learning Activity Center (PKBM). PKBM can organize Equality Education Package A/B/C, the legality is regulated in Law no. 20/2003. In organizing this package program, teaching and learning activities in PKBM are guided by teaching staff who are called tutors. However, it is found that tutors who have diverse educational backgrounds, so the skills and teaching methods applied are still very simple and monotonous. This was also found in the PKBM Bumi Literasi located in Sigara-gara Village, Patumbak District, Deli Serdang Regency. Based on the results of interviews and on-site observations, the tutors explained that such teaching methods had an impact on decreasing the learning interest of the learning community. Based on this, the team assumed the need to introduce the Student Centered Learning (SCL) teaching method to all PKBM Bumi Literasi tutors. So, the purposes of community service are to 1) introduce the methods, benefits, and functions of SCL to tutors, 2) explain the types of SCL methods, and 3) provide strategies and recommendations in applying SCL in the learning process. From the results of community service activities, the N-gain number is 0.70, which is normalized into the high category. This shows that after getting knowledge and exposure to material about SCL, the knowledge and teaching ability of PKBM Literacy tutors has increased